Management of Brain Metastases with Preoperative Radiosurgery - Topkan, Erkan; Kucuk, Ahmet; Senyurek, Sukran; Sezen, Duygu; Durankus, Nulifer Kilic; Akdemir, Eyub Yasar; Ikiz, Esma Didem; Bolukbasi, Yasemin; Pehlivan, Berrin; Selek, Ugur (Highlights on Medicine and Medical Research Vol. 2, 2021)
Representing the most common intracranial tumors brain metastases (BMs) are diagnosed in nearly 30% to 54% of all patients during or after their treatment courses against solid cancers. Although the prognosis of BM patients is extremely poor with an estimated median OS of usually less than 7 months. Nevertheless, nowadays some patients’ groups may experience significantly longer survival durations after the implementation of effective systemic and local therapies, such as surgery and radiotherapy (RT). Currently, the noteworthy alternatives for the management of BMs include the neurosurgery, whole-brain RT (WBRT), definitive SRS, postoperative SRS, systemic chemotherapy, targeted therapies, immunotherapy and their various blends. Regarding the local treatment maneuvers, the well-recognized severe neurotoxicity of WBRT and the augmented risk for radionecrosis and leptomeningeal dissemination after postoperative SRS and the ineligibility of certain patients during the postoperative period mandated the search for safer and potentially more effective treatment alternatives for such patients’ group. In this regard, the novel preoperative SRS (PO-SRS) was proposed to provide at least comparable local control rates with lesser radionecrosis and leptomeningeal dissemination risk. The present chapter details the conceivable rationale and available proof for the novel PO-SRS in the management armamentarium of the cancer patients presenting with BMs.